Influence of Feeding of Diverse Forms of Trace Minerals on Nutrient Utilisation and Blood Parameters in Crossbred Cows - Choudhary, Sunil Dutt; Choudhary, Sheela; Yadav, Poonam; Kumar, Rajesh; Meena, Vikas Kumar (Indian Journal of Animal Nutrition, 2017)
An experiment was conducted to evaluate the effect of inorganic and organic (chelated) trace minerals supplementation on nutrient utilization and blood parameters in crossbred cows. Fifteen crossbred cows were randomly divided in three groups of 5 animals each. In group G1, the animals were fed on wheat straw based diet and did not receive mineral mixture whereas the animals of experimental group 2 (G2) and group 3 (G3) were feda similar basal feed along with inorganic and organic trace minerals, respectively. A digestion trial of 7 days duration was conducted during 60 d of feeding trial. The supplementaion of inorganic and organic trace minerals improved (P